2018
DOI: 10.1139/facets-2017-0081
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic species diversity and reproductive isolation among sympatric lineages ofStrongylocentrotussea urchins in the northwest Atlantic

Abstract: Distinguishing between intra-and inter-specific variation in genetic studies is critical to understanding evolution because the mechanisms driving change among populations are expected to be different than those that shape reproductive isolation among lineages. Genetic studies of north Atlantic green sea urchins Strongylocentrotus droebachiensis (Müller, 1776) have detected significant population substructure and asymmetric gene flow from Europe to Atlantic Canada and interspecific hybridization between S. dro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 63 publications
2
21
0
Order By: Relevance
“…They have been rarely used in this context, except for the deeper lineages that were initially easily distinguished even by the slowly evolving allozyme markers. Evolution of incompatibility over a single glacial cycle appears unlikely, and for young lineages, observations of haplotype mixing plausibly reflect merging of the refugial ancestries (however, see Addison & Kim, 2018). This was inferred in Hiatella L in a broad sector of the NW Atlantic range (Laakkonen, Strelkov, & Väinölä, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…They have been rarely used in this context, except for the deeper lineages that were initially easily distinguished even by the slowly evolving allozyme markers. Evolution of incompatibility over a single glacial cycle appears unlikely, and for young lineages, observations of haplotype mixing plausibly reflect merging of the refugial ancestries (however, see Addison & Kim, 2018). This was inferred in Hiatella L in a broad sector of the NW Atlantic range (Laakkonen, Strelkov, & Väinölä, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Although secondary contacts of young lineages seem to be common in the data, so far there is little conclusive evidence of such repeated process over a broader time frame. A broader genomic sampling should elucidate this, and interesting histories to be addressed could involve Gammarus setosus and Balanus crenatus , apart from the ongoing genomics of Strongylocentrotus , which provides insights also to rapid reproductive isolation and habitat segregation in contacts of young lineages ( Addison & Kim, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, previous laboratory results indicated that the sympatric areas were limited to the Huilai-adjacent sea area (He et al, 2012). It is important to determine the areas of sympatry and understand the ecological differences of sympatric cryptic species, which are valuable systems for exploring gene exchange, introgressive hybridization, and species differentiation (Michel et al, 2010;Addison and Kim, 2018).…”
Section: Introductionmentioning
confidence: 99%